Proceedings. Eighth IEEE Real-Time and Embedded Technology and Applications Symposium
DOI: 10.1109/rttas.2002.1137394
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing CAN response-time jitter by message manipulation

Abstract: Delay variations (jitter)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 14 publications
0
35
0
Order By: Relevance
“…Tindell's seminal research heavily influenced the design of on-chip CAN peripherals such as Motorola msCAN (Motorola, 1998) and has lead to a large body of work into schedulability theory and error models for CAN (Punnekkat et al, 2000;Nolte et al, 2002Nolte et al, , 2003Broster et al, 2002Broster et al, , 2005Hansson et al, 2002;Broster and Burns, 2003), including at least two PhD theses (Broster, 2003;Nolte, 2006). Overall, this research into CAN scheduling has been cited in over 200 2 subsequent papers.…”
Section: Research and Real-time Analysismentioning
confidence: 99%
“…Tindell's seminal research heavily influenced the design of on-chip CAN peripherals such as Motorola msCAN (Motorola, 1998) and has lead to a large body of work into schedulability theory and error models for CAN (Punnekkat et al, 2000;Nolte et al, 2002Nolte et al, , 2003Broster et al, 2002Broster et al, , 2005Hansson et al, 2002;Broster and Burns, 2003), including at least two PhD theses (Broster, 2003;Nolte, 2006). Overall, this research into CAN scheduling has been cited in over 200 2 subsequent papers.…”
Section: Research and Real-time Analysismentioning
confidence: 99%
“…The seminal work of Tindell et al lead to a large body of research into scheduling theory for CAN (Rufino et al, 1998;Broster et al, 2002;Broster and Burns, 2003;Broster, 2003;Broster et al, 2005;Ferreira et al, 2004;Nolte et al, 2002;Nolte et al, 2003;Nolte, 2006), and was used as the basis for commercial CAN schedulability analysis tools (Casparsson et al, 1998). Davis et al (2007) found and corrected significant flaws in the schedulability analysis given by Tindell and Burns, (1994), , and Tindell et al, (1995).…”
Section: Related Workmentioning
confidence: 99%
“…However, in our previous work [6,7] we represent the number of stuff-bits as a distribution. By using a distribution of stuff-bits instead of the worst-case number of stuff-bits, we obtain a distribution of response-times allowing us to calculate less pessimistic (compared to traditional worst-case) response-times based on probability.…”
Section: New Approachmentioning
confidence: 99%
“…From [7] we can extract 9 different distributions of stuff-bits depending on the number of bytes of data in the CAN message frame. We define …”
Section: New Approachmentioning
confidence: 99%
See 1 more Smart Citation